Periimplant bone changes in different abutment heights and insertion timing in posterior mandibular areas: Three‐year results from a randomized prospective clinical trial. Issue 2 (9th December 2020) - Borges, Tiago; Montero, Javier; Leitão, Bruno; Pereira, Miguel; Galindo‐Moreno, Pablo
Abstract: Aim: To compare the influence of the abutment height and its insertion timing on the marginal bone change (MBC) variation of implants placed at posterior mandibular partial edentulous areas in a medium follow‐up period. Material and methods: This randomized clinical trial (RCT) comprised a sample of patients with posterior mandibular edentulous areas, treated with at least two implants and distributed into three groups: implants connected to a 2 mm height abutment during the surgical stage (Group A); implants connected to a 1 mm height abutment during the surgical stage (Group B); and implants connected to a 2 mm height abutment after 2 months (Group C). Clinical and radiographic measurements were performed during a 36‐month period (T4). The MBC was set as the main variable in study. Statistical significance was set at 0.05. Results: A total of 29 subjects and 59 implants were enrolled in this study. A mean MBC of 0.35 ± 0.46 mm, 0.60 ± 0.81 mm, and 0.71 ± 0.90 mm was computed for groups A, B and C, respectively, at T4. Significant differences were found between groups A and C in terms of MBC variation after 3 years of treatment ( p  = .048). Multiple linear regression analysis showed a significant influence of the first‐year MBC and the abutment insertion timing has independent predictor variables for the MBC assessed at T4. Conclusion: The installation of 2‐mm prosthetic abutments, at the time of implant placement, in areas with limited keratinized mucosa presents as a favorable treatment option in terms of periimplant marginal bone maintenance.